Ab initio and density functional theory study of the electronic structure of rhenium complexes with noninnocent dioxolene ligands: Localized vs delocalized valence states. Issue 23 (17th July 2019) - Dmitriev, Alexey A.; Gritsan, Nina P.
Abstract: The dioxolene type ligands (Diox) derived from ortho ‐quinones are the most widely studied redox noninnocent ligands existing in the dianionic (Cat), anion radical (SQ) or neutral (Q) forms although a highly delocalized electronic structure is also possible. For [ReO(Diox)2 PPh3 ] − (2 ) and [ReCl3 (Diox)PPh3 ] (3 ) complexes, the Re V ‐ Cat 2 and Re IV ‐ SQ localized valence states were proposed on the basis of their XRD structures. To understand in detail the electronic structure of these complexes, we performed a series of the all‐electron calculations at the DKH2‐CASSCF/CASPT2 and DKH2‐CASSCF/NEVPT2 levels taking into account scalar relativistic and spin‐orbit effects. All calculations predicted that2 has a singlet ground state with a predominant contribution of a single electronic configuration with doubly occupied molecular orbitals being pure o ‐quinone LUMOs of both Diox ligands that corresponds to the Re V ‐ Cat 2 valence state. Complex3 has a triplet ground state with four electronic configurations contributing mainly into its wavefunction and differing by the occupation of bonding and antibonding combinations of the o ‐quinone LUMO and rhenium d‐AO with nearly equal contributions. This leads to the empirical "metrical oxidation state" of dioxolene ligand being −1 that is usually referred to the Re IV ‐SQ oxidation state. However, in fact, the negative charge on the Diox ligand is mainly provided by a pair of electrons on the bonding MO. The standard DFT calculations entirely fail to correctly predict the ground state multiplicity for3 . Abstract : Rhenium complexes with redox noninnocent dioxolene ligands attract significant attention because of their promising catalytic, magneto‐, and electrochemical properties. Nonetheless, reliable, high‐level computational studies of such complexes are not currently available in literature. High‐level ab initio multireference and DFT calculations for two rhenium complexes are presented here, highlighting the limitations of DFT as tool for studying this kind of compounds.